Beetle and wētā community responses to mammal eradication on Maungatautari, Waikato, New Zealand. Issue 4 (1st October 2020) - Watts, Corinne; Innes, John; Cave, Vanessa; Thornburrow, Danny; Thorpe, Stephen
ABSTRACT: Predation by introduced mammals frequently limits abundance of New Zealand's native invertebrates. We investigated responses of beetle and wētā communities to mammal eradication at two fenced forest sites at Maungatautari. Ground-dwelling beetle abundance, but not species richness, increased inside the southern exclosure two years after all mammals were eradicated. In the next 5 years, when all mammals except mice were eradicated from all of Maungatautari, beetle abundance and species richness were frequently higher in the mouse-free southern exclosure. Beetle community composition changed after mammal eradication, and over time with increasing mice densities outside the southern exclosure. Large, predatory, and native beetles showed the most differences between inside and outside the southern exclosure over some years. Wētā were more responsive to mammal removal than beetles. Wētā abundances both inside and outside the southern exclosure were similar when most mammals were eradicated and mice were controlled to low numbers. However, wētā declined in the following 2 years outside the southern exclosure when mouse abundance increased. Abiotic and biotic factors affecting the beetle and wētā communities are complex and interactions poorly understood. This study indicates that climate and predation by native fauna are likely to be important factors.